Strategi Pengembangan Mutu Lembaga Pendidikan Pesantren Dengan Pedoman Kurikulum Darurat COVID-19 - Fahris, Fahris; Siswanto, Romy (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
COVID-19 has drastically changed the way people live and activities, including in the field of education. Educational institutions around the world, especially in Islamic boarding schools, are forced to face challenges to maintain the quality of education in the midst of this pandemic. This paper aims to explain the quality development strategy of educational institutions with covid-19 emergency curriculum guidelines. This study uses a qualitative descriptive approach with a case study method at a junior secondary education institution in one of the pensantren in Madura.